In Vitro Antimicrobial Activity of Bawang Batak Bulbs (Allium Chinense G. Don) Against Methicillin-Resistant Staphylococcus Aureus - Aretha, Tiasarah; Jusuf , Nelva Karmila (Talenta Publisher, 2019)
Introduction: Staphylococcus aureus infection can cause pyoderma. These days there is a shift in Staphylococcus aureus sensitivity to antibiotics that is marked by the existence of Methicillin-Resistant Staphyloccus aureus, so alternative therapy that is herbal medicine might be needed. There are a lot of medicinal plants in Indonesia, but until today the usage is still minimum. One of the plant genus that is already being used is allium that had been known to have antimicrobial activity. The genus allium that is consumed a lot by Indonesians especially people of North Sumatra is bawang batak (Allium chinense G.Don.). This study is conducted to assess the antimicrobial activity of bawang batak bulbs in several concentrations to MRSA. Methods: This research is an experimental research with agar diffusion method. The extracts were divided into six groups: extracts in concentration level of 6.25%, 12.5%, 25%, 50%, 100% and a negative control (DMSO). The sample size is four per group with total sample of 24. Results: The results showed that the inhibition of bacterial growth occured at the concentration levels of 50% and 100% with inhibition zone diameters of 8.695 mm and 10.545 mm respectively. Extracts with concentration levels of 25%, 12.5% and 6.25% did not show any inhibition. Conclusion: Bawang batak bulbs extract can be used to inhibit the growth of MRSA